What Determines Post-IPO Market Performance: Evidence From Turkish IPOs - Macit, Fatih; Sekreter, Ahmet; Ada, Selver Seda; Simsek, Esra (Bulletin of Business and Economics (BBE), 2015)
In this paper we investigate the determinants of the short-run post-IPO market performance of IPO stocks for Turkish markets. We looked at various firm specific accounting and IPO related variables namely the ratio of operating profit to total sales, the ratio of total debt to total assets, IPO size, public float, the ratio of shares that are purchased by foreign investors, and the market value to book value ratio. We find that IPO size appears to be the most important variable in determining the post-IPO market performance of IPO stocks. Large IPO’s tend to have a better post-IPO market performance. Besides that firms with a larger debt ratio are expected to show a better performance in the short-run. It is seen that as public float increases IPOs tend to show a poorer performance.